Saving Mr. Banks - Hancock, John Lee; Marcel, Kelly, 1974-; Smith, Sue (Children's story writer); Thompson, Emma; Hanks, Tom; Giamatti, Paul; Schwartzman, Jason, 1980-; Whitford, Bradley; Farrell, Colin, 1976-; Walt Disney Productions; Buena Vista Home Entertainment (Firm) (Los Angeles, CA : Buena Vista Home Entertainment, 2014)
When P.L. Travers travels from London to Hollywood in 1961 to discuss Walt Disney's desire to bring her character, Mary Poppins, to the motion picture screen, Disney meets a woman not only suspect of the impresario's concept for the film, but struggling with her own past. During her stay in California, Travers' reflects back on her difficult childhood in 1906 Australia.
Originally released as a motion picture in 2013.
Bonus features: Deleted scenes; "Nanny song".
Emma Thompson, Tom Hanks, Paul Giamatti, Jason Schwartzman, Bradley Whitford, Colin Farrell.
Rating: PG-13; for thematic elements including some unsettling images.
DVD; widescreen (2.40:1); Dolby Digital 5.1; NTSC, region 1; dual layer.
English, Spanish or French dialogue; Spanish or French subtitles; English SDH; English DVS.
Keywords: Travers, P. L. -- 1899-1996 -- Drama; Disney, Walt, -- 1901-1966 -- Drama; Mary Poppins (Motion picture) -- Drama; Feature films; Biographical films; Comedy films; Films for the hearing impaired; Films for people with visual disabilities